Geographical Assessment of the Tourism Circumstances in Dhi Qar Governorate - Alaa Rabea Al-Husseini , Assist. Lect . Fatima (Basra studies journal, 2025)
Tourism is no longer just a recreational activity for people but has now become an export industry that plays an important role in the country’s economic development. Since the study area has many basic components for tourism attraction and economic sector development, it must be optimally exploited, developed and all obstacles facing tourism development removed. Hence the necessity of studying all the climate elements and their role in the establishment and development of the tourism industry. This study included two sections, the first of which dealt with the study of the tourism climate and climate data at the Nasiriyah climate station, and then the geographical analysis of the elements of the tourism climate in Dhi Qar Governorate and explaining the role of each element in tourism. The second section used special equations to evaluate the tourism climate in Dhi Qar Governorate, including the effective temperature index equation ET, the wind cooling index K, and the tourism climate comfort index TCCI. And applying each of them to the climate data of the study area and determining its role in the activity of the tourist movement and its development in each month and season of the year in terms of it being an ideal climate that helps attract tourists and is suitable for tourist activities or the opposite".